Direct spray-coating of highly robust and transparent Ag nanowires for energy saving windows. (August 2019) - Lin, Sen; Wang, Haiyang; Zhang, Xuenan; Wang, Dong; Zu, Di; Song, Jianan; Liu, Zhenglian; Huang, Ya; Huang, Kai; Tao, Nian; Li, Ziwei; Bai, Xiaopeng; et al.
Abstract: A large portion of energy consumed in buildings via infrared (IR) radiation through windows, therefore, IR blocking protection or low-emission (Low-E) window is urgently required for more energy-saving buildings. While most Low-E glass require complex and high-cost vacuum sputtering coatings, IR blocking layer that can be directly coated with cost-effective and large-scale process is desired. Herein, we report facile and scalable processing of silver nanowires/polyvinyl butyral (AgNWs/PVB) coatings for high performance Low-E windows. The spay process can be applied to create reliable IR modulation layer directly onto normal glass, and have also been expanded to roll-to-roll coating on flexible plastics. The AgNWs/PVB coating showed high transmittance of visible light (∼83.0%), high reflectivity of mid-IR (∼69.8%), low emissivity, as well as reliable chemical and mechanical durability. Graphical abstract: Image 1 Highlights: A large portion of energy consumption escapes from building via IR radiation through windows. We propose a solution spraying technology to fabricate highly-transparent Low-E window-coating materials. We have successfully sprayed our coating material on one window of a real building for architectural-scale verification. The IR radiation for the treated window in winter have been reduced by 32.8%. The as-prepared AgNWs/PVB coating material shows high reliability and excellent durability.